Brucella-Induced Ruptured Infrarenal Dissecting Abdominal Aortic Aneurysm - Ramachandran Nair, Harishankar (Aorta (Stamford), 2019)
Mycotic aneurysms, often saccular, accounting for approximately 2.5% of all abdominal aortic aneurysms, possess increased risk of rupture, uncontrolled sepsis, and protracted hospital stay and are associated with high morbidity and mortality. The authors report the case of a 49-year-old female with no known comorbidities who presented with free rupture of an infrarenal dissecting mycotic aneurysm and underwent emergent open repair successfully. The etiological agent, Brucella melitensis , a Gram-negative zoonotic coccobacillus, is rarely reported to cause mycotic aneurysm.